2023
DOI: 10.1002/adem.202201712
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Mechanisms and Thermal Models of Chemically Incompatible Metals (Mo/W–Cu): A Review

Abstract: Molybdenum (Mo) and tungsten (W) are elements of the same family with similar properties, and both of them have high hardness, mechanical strength, and electrochemical corrosion properties, [1] which are widely used in the research and application of hightemperature and arc ablation-resistant materials. [2,3] Mo-Cu and W-Cu alloys are typical pseudoalloys. [4] There is almost no reaction between tungsten and copper, molybdenum and copper in the sintering process, and almost no intermetallic compounds are produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that the integration of efficient thermally and electrically conductive carbon‐based fillers, including carbon nanotubes (CNT), [ 6 ] graphene oxide [ 7,8 ] and carbon fiber (CF), [ 9 ] as well as metal‐based fillers such as Cu [ 10 ] and Ag [ 11,12 ] into epoxy resin to establish interconnected networks, which apparently facilitated the movement of phonons and electrons within the epoxy resin, thus boosting its thermal and electrical conductivity. [ 13 ] Especially, CNT exhibit ultrahigh thermal conductivity (TC) from 2800 to 6000 W m −1 K −1 and offer a great advantage in EMI shielding applications on account of their high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the integration of efficient thermally and electrically conductive carbon‐based fillers, including carbon nanotubes (CNT), [ 6 ] graphene oxide [ 7,8 ] and carbon fiber (CF), [ 9 ] as well as metal‐based fillers such as Cu [ 10 ] and Ag [ 11,12 ] into epoxy resin to establish interconnected networks, which apparently facilitated the movement of phonons and electrons within the epoxy resin, thus boosting its thermal and electrical conductivity. [ 13 ] Especially, CNT exhibit ultrahigh thermal conductivity (TC) from 2800 to 6000 W m −1 K −1 and offer a great advantage in EMI shielding applications on account of their high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%